2019
DOI: 10.17755/esosder.450201
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrenci̇leri̇ni̇n Fen Bi̇li̇mleri̇ Dersi̇nde Kendi̇ Kendi̇ne Öğrenme Beceri̇leri̇ni̇n Yordanmasinda Kayginin Rolü

Abstract: Araştırmada, fen bilimleri dersi öğretiminin en önemli duyuşsal alan değişkenlerinden biri olan kaygının ortaokul öğrencilerinin kendi kendine öğrenmeyi planlama ve güvenme becerileriyle olan ilişkileri incelenmiştir. Araştırmanın çalışma grubunu 2017-2018 eğitim öğretim yılında Siirt İl merkezde İl Milli Eğitim Müdürlüğüne bağlı ortaokullarda öğrenim gören 79'u kız, 109'u erkek toplam188 ortaokul öğrencisi oluşturmaktadır. Araştırmada veriler, Aydede ve Kesercioğlu (2009) tarafından geliştirilmiş olan "Kendi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These results show that there is no significant difference between the mean scores of the secondary school students in terms of self-learning with technology and test anxiety inventory according to gender variable. These findings are supported by Kahyaoğlu et al (2019), Avcı and Kırbaşlar (2017), Akça (2017 and Kağıtçı (2014). Akça (2017) investigated the correlation between gender and test anxiety by administering the "Science Anxiety Scale" to 600 secondary school students.…”
Section: Discussionmentioning
confidence: 55%
“…These results show that there is no significant difference between the mean scores of the secondary school students in terms of self-learning with technology and test anxiety inventory according to gender variable. These findings are supported by Kahyaoğlu et al (2019), Avcı and Kırbaşlar (2017), Akça (2017 and Kağıtçı (2014). Akça (2017) investigated the correlation between gender and test anxiety by administering the "Science Anxiety Scale" to 600 secondary school students.…”
Section: Discussionmentioning
confidence: 55%
“…There was no significant difference between students' science anxiety in terms of gender. Looking at the literature, it was seen that there was no significant difference between female and male students' science anxiety in studies examining the effect of gender on science anxiety (Avci & Kirbaslar, 2017;Kahyaoglu, Birel & Yetisir, 2019;Udo, Ramsey & Mallow, 2004;Ulucinar-Sagir, 2012). Studies show that science anxiety varies based on gender, and female students are more anxious (Akgun, Gonen & Aydin, 2007;Anderson & Clawson, 1992;Mallow, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is essential to determine the anxiety and motivation levels of the students towards science course and the variables that affect them and take the necessary precautions. A review of studies on science anxiety in Turkey investigates the factors affecting students' science anxiety (Avci & Kirbaslar, 2017) and the role of anxiety as a predictor of secondary school students' self-learning skills (Kahyaoglu, Birel & Yetisir, 2019) were found. In addition, the relationship between science anxiety and attitude towards science lesson (Ulucinar-Sagir, 2012), science anxiety and mental risk-taking behaviours (Akca, 2017), anxiety towards science course and academic achievement (Avci & Kirbaslar, 2017), anxiety towards science course and science learning orientations (Yolagiden & Bektas, 2018) was investigated.…”
Section: The Importance Of the Studymentioning
confidence: 99%
“…As a result of the study, it has been shown that there is a moderate, negative, and significant relationship between the students' scores of anxiety about the science lesson and their attitude scores towards this lesson. In their study, Kahyaoğlu, Birel and Yetişir (2019) determined that there was a significant negative relationship between self-learning planning skills and confidence skills in science lessons and science anxiety levels. They also stated that as science anxiety levels of secondary school student's increase, their ability to plan self-learning and confidence in science lessons decreases.…”
Section: Discussionmentioning
confidence: 99%